The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1155/2020/7808535
|View full text |Cite
|
Sign up to set email alerts
|

Color Stability of Glass Ionomer Cement after Reinforced with Two Different Nanoparticles

Abstract: Aim. This study aimed to compare the staining characteristics of a commercially available restorative glass ionomer cement to a formulation reinforced by the addition of carbon nanotubes and another formulation reinforced by the addition of silver nanoparticles to the powder of the same cement. Methodology. Twenty samples each of a control glass ionomer cement (PULPDENT® Glass Fill®, Pulpdent Corp. Watertown, MA, USA), control cement reinforced with 0.0006 gm (0.03% by weight) of carbon nanotubes (Sigma Aldric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 19 publications
(40 reference statements)
0
2
0
3
Order By: Relevance
“…A study done by Bhattacharya and et al concluded that cention performed better color stability when compared to conventional GIC [ 1 ]. By contrast, Pani et al reported that the inclusion of strengthening materials leads to a notable reduction in the color stability of glass ionomer cement [ 17 ]. Another study by Bajpai et al presented a contrasting view, suggesting that the handling and mixing involved in the preparation of a material, particularly with powder and liquid components, pose an elevated risk of incorporating air bubbles.…”
Section: Discussionmentioning
confidence: 99%
“…A study done by Bhattacharya and et al concluded that cention performed better color stability when compared to conventional GIC [ 1 ]. By contrast, Pani et al reported that the inclusion of strengthening materials leads to a notable reduction in the color stability of glass ionomer cement [ 17 ]. Another study by Bajpai et al presented a contrasting view, suggesting that the handling and mixing involved in the preparation of a material, particularly with powder and liquid components, pose an elevated risk of incorporating air bubbles.…”
Section: Discussionmentioning
confidence: 99%
“…A maioria dos trabalhos incluídos nesta revisão relatam a susceptibilidade do CIV convencional ao manchamento mediante imersão em variadas soluções corantes e protocolos experimentais (Adusumilli et al, 2016;Boscarioli et al, 2002;Chakravarthy & Clarence, 2018;Debner et al, 2000;Fay et al, 1999;Jafarpour et al, 2019;Pimenta et al, 1997;Saito et al, 2000;Wang & Huang, 2014). Em contrapartida, alguns artigos da presente revisão observaram estabilidade de cor do CIV convencional em comparação a outros materiais restauradores (Bezgin et al, 2015;Kale et al, 2019;Li et al, 2009;Pani et al, 2020;Prabhakar et al, 2013).…”
Section: Discussionunclassified
“…Por outro lado, a maior estabilidade de cor do CIV convencional foi observada experimentalmente em vários trabalhos (Bezgin et al, 2015;Kale et al, 2019;Li et al, 2009;Pani et al, 2020;Prabhakar et al, 2013). A maior resistência às alterações de cor do CIV pode ser atribuída à capacidade de pigmentação das soluções corantes e às propriedades inerentes ao material, destacando-se a sorção de água (Bezgin et al, 2015) e as características das partículas de vidro do CIV (Kale et al, 2019).…”
Section: Discussionunclassified
“…16 Semen ionomer kaca memiliki sifat mekanik dan estetika yang kurang baik, namun hal ini tidak membatasi penggunaanya sebagai bahan restorasi, terutama untuk gigi sulung. 8,17 Seleksi warna restorasi yang baik menjadi tahapan penting untuk mendapatkan hasil restorasi yang memuaskan. Salah satu cara pengukuran warna yang akurat ialah dengan menggunakan spektrofotometer yang mengukur pantulan spektral atau kurva transmisi dari suatu spesimen.…”
Section: Pendahuluanunclassified